Motor-cognitive coupling is impaired in children with mild or severe forms of developmental coordination disorder - Abdollahipour, Reza; Valtr, Ludvík; Banátová, Kamila; Bizovská, Lucia; Klein, Tomáš; Svoboda, Zdeněk; Steenbergen, Bert; Wilson, Peter Henry (Frontiers in Human Neuroscience, 2023)
Children with developmental coordination disorder (DCD) show deficits in motor-cognitive coupling. However, it remains unclear whether such deficits depend on the severity of DCD. The aim of this study was to examine cognitive-motor coupling under different levels of inhibitory control in children with severe (s-DCD) or moderate DCD (m-DCD), compared with typically-developing children (TDC). The performance of 29 primary-school children aged 6-to-12 years with s-DCD (Mage = 9.12 ± 1.56 years), 53 m-DCD (Mage = 8.78 ± 1.67 years), and 201 TDC (Mage = 9.20 ± 1.50 years) was compared on a double jump reaching task (DJRT) paradigm, presented on a large 42inch touchscreen. The task display had a circular home-base, centred at the bottom of the display, and three target locations at radials of -20°, 0°, and 20°, 40cm above the home-base circle. For the standard double-jump reaching task (DJRT), children moved their index finger from home-base circle to touch the target stimulus as fast as possible; 20% were jump trials where the target shifted left or right at lift-off. For the anti-jump reaching task (AJRT), 20% of trials required an anti-jump movement, touching the contralateral target location. While no group differences were shown on the DJRT, the DCD group were slower to complete reaching movements than the TDC group on AJRT; on the latter, the two DCD sub-groups were not shown to differ. Results confirm the presence of motor inhibition deficits in DCD which may not be dependent on the motor severity of the disorder.